THE WOMEN’S MOVEMENT: A TWO-HUNDRED YEAR SYNOPSIS - Dupuis, Elaine M. (Journal of Dharma, 1991)
It is not an understatement to say that we do not know ourselves. However, any woman who undertakes the study of the women’s movement in Judaeo-Christian societies over the last two hundred years, is faced with a self-revelation. If the struggle of women to be heard went on for millennia without success under ’patriarchal’ rule, many reasons can now be enumerated, not the least of which is the fact that, in their political isolation from each other, they did not gather or record their history and, thus, had no social sense of their own communion and continuity.